Identifying Interactive Toys’ Key Characteristics for Intellectual Disabilities Children in Special School - Flora, Christina (ULTIMART Jurnal Komunikasi Visual, 2024)
The rising prevalence of intellectual disabilities in Indonesia, notably in Jakarta, raises pressing concerns. Many affected individuals, particularly children, face social challenges that need to be addressed and implemented in education, thus the role of Special Schools, which unfortunately often rely on teaching methods that are deemed unsuitable for intellectually disabled children. Therefore, it is imperative to design a media that is suitable for teaching social relations in Special Schools. The use of interactive toys in play activities has proven to be beneficial in education, due to their contribution to children's emotional and cognitive development. This research aims to identify toy characteristics that enhance learning for elementary students with intellectual disabilities, providing recommendations for developing interactive educational tools for teachers. The methods used in this research will be observation and literature studies. Findings show that it is important to consider the use of color, materials, as well as several engagement aspects in designing interactive toys for Special Schools' elementary students. Keywords: interactive; toys; intellectual disabilities; game lenses; special school